2015
DOI: 10.1155/2015/257057
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidiarrheal Activity of Methanolic Extract ofMaranta arundinaceaLinn. Leaves

Abstract: Diarrhea is one of the most common causes for thousands of deaths every year. Therefore, identification of new source of antidiarrheal drugs becomes one of the most prominent focuses in modern research. Our aim was to investigate the antidiarrheal and cytotoxic activities of methanolic extract of Maranta arundinacea linn. (MEMA) leaves in rats and brine shrimp, respectively. Antidiarrheal effect was evaluated by using castor oil-induced diarrhea, enteropooling, and gastrointestinal motility tests at 200 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 23 publications
2
42
0
5
Order By: Relevance
“…The production of ricinoleic acid in the intestine results in inflammation and irritation of the mucosa and the release of mediators like prostaglandins that prevent fluid and electrolyte absorption and increase the intestinal peristaltic movements, this series of events ultimately leading to diarrhea [14,15,18]. By using the castor oil-induced enteropooling model and the charcoal transit method, we showed that the probiotic mixture decreased both the accumulation of fluid into the lumen and intestinal motility.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The production of ricinoleic acid in the intestine results in inflammation and irritation of the mucosa and the release of mediators like prostaglandins that prevent fluid and electrolyte absorption and increase the intestinal peristaltic movements, this series of events ultimately leading to diarrhea [14,15,18]. By using the castor oil-induced enteropooling model and the charcoal transit method, we showed that the probiotic mixture decreased both the accumulation of fluid into the lumen and intestinal motility.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that castor oil induces diarrhea through its active metabolite, ricinoleic acid [14,15,18]. The production of ricinoleic acid in the intestine results in inflammation and irritation of the mucosa and the release of mediators like prostaglandins that prevent fluid and electrolyte absorption and increase the intestinal peristaltic movements, this series of events ultimately leading to diarrhea [14,15,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, castor oil is metabolized into ricinoleic acid in the gut, which causes irritation and inflammation in the intestinal mucosa, resulting in the release of inflammatory mediators (prostaglandins). The released prostaglandins initiate vasodilation, smooth muscle contraction and mucus secretion in the small intestines, in experimental it can be considered to be good diarrheagenic agents [27].…”
Section: Sangkareho Leaves (Callicarpa Longifolia Lam) Accordingmentioning
confidence: 99%
“…100% was considered as the total number of feces of control group. The activity was expressed as percent inhibition of diarrhea [28][29].…”
Section: In Vivo Anti-diarrheal Activity Testmentioning
confidence: 99%